2018
DOI: 10.1111/joic.12556
|View full text |Cite
|
Sign up to set email alerts
|

Management of post‐myocardial infarction ventricular septal defects: A critical assessment

Abstract: Background: Post-myocardial infarction (MI) ventricular septal defects (PIVSD) are an uncommon but life-threatening complication of acute MI. Although surgical closure has been the standard of care, mortality, and recurrence of VSD remain high even after emergent surgery. Transcatheter VSD closure (TCC) devices have become an alternative or adjunct to surgical closure.Methods: Online database search was performed for studies that included adults with PIVSD who underwent medical treatment (MT) alone, surgical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 46 publications
1
47
0
1
Order By: Relevance
“…Maltais et al suggest that utilizing TCC for defects larger than 15 mm puts the patient at risk for device embolization or recurrent VSD 13 . Omar et al 14 recently found overall mortality was lower in the TCC group than the surgery group. However, the authors emphasize that either TCC or surgery are superior to medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Maltais et al suggest that utilizing TCC for defects larger than 15 mm puts the patient at risk for device embolization or recurrent VSD 13 . Omar et al 14 recently found overall mortality was lower in the TCC group than the surgery group. However, the authors emphasize that either TCC or surgery are superior to medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of post-MI VSD is challenging. The timing of intervention and the treatment approach continues to be an area of debate, depending on the type and size of the defect, clinical condition of the patient, and technical expertise [8][9][10]. Surgical management has been the standard treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital VSDs are less common in adults due to spontaneous closure in most cases, however, VSDs can also be acquired from acute myocardial infarction or following surgical or interventional procedures in the heart. [4][5][6] Clinical presentation of VSDs is dependent upon their size and shunt severity. Indications for VSD closure include hemodynamically significant shunt, significant or worsening aortic regurgitation, and history of endocarditis.…”
Section: Discussionmentioning
confidence: 99%